2013
DOI: 10.5539/gjhs.v6n1p215
|View full text |Cite
|
Sign up to set email alerts
|

Novice Nurses' Experiences of Unpreparedness at the Beginning of the Work

Abstract: Introduction:Unpreparedness of novice nurses during the process of transition to their professional role can has broad consequences for the nurse and health care system and leads to reduction of the quality of patient care. This study has been carried out with the aim of investigating the experiences of the unpreparedness of novice nurses.Method:This study was conducted qualitatively by using conventional content analysis. Participants were 21persons including 17 novice nurses, 2 supervisors, and 2 experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 28 publications
(36 reference statements)
2
39
0
Order By: Relevance
“…Consistent with our results, previous studies show how SNS experience different feelings about the rotation process throughout the various units: functional impairment, communication problems and inability to take responsibility, stress related to the workload, interpersonal relationships and lack of support, affecting their physical and mental health (22,23) .…”
Section: Building the First Contactsupporting
confidence: 92%
“…Consistent with our results, previous studies show how SNS experience different feelings about the rotation process throughout the various units: functional impairment, communication problems and inability to take responsibility, stress related to the workload, interpersonal relationships and lack of support, affecting their physical and mental health (22,23) .…”
Section: Building the First Contactsupporting
confidence: 92%
“…For example, being comfortable asking for help and being able to communicate with colleagues, patients and their families, and patients of the opposite sex (Hezaveh, Rafii, & Seyedfatemi, 2014;Missen, McKenna, & Beauchamp, 2015). For example, being comfortable asking for help and being able to communicate with colleagues, patients and their families, and patients of the opposite sex (Hezaveh, Rafii, & Seyedfatemi, 2014;Missen, McKenna, & Beauchamp, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has shown that NGN, following the start of work, would realize that they are not ready enough and there are contradictions between the knowledge and skills acquired during education and the behaviors expected of them at work. Therefore, some NGNs are not able to handle such conflicts and leave the profession (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Beginning work in the health profession, particularly for nurses, is associated with more stress than other professions (5). In this regard, Hezaveh et al (4) suggest that probably newly graduated nurses lack the required preparedness for dealing with the working complex conditions (10). Currently, Iran, like many countries, is exCopyright © 2018, Shiraz E-Medical Journal.…”
Section: Introductionmentioning
confidence: 99%